EFEKTIVITAS PENDEKATAN STEAM BERBASIS PROJECT BASED LEARNING DALAM MENINGKATKAN PEMAHAMAN KONSEP MATEMATIS MATERI PECAHAN - Annisya, Misrina, Samsil Bahri (FKIP UMN ALWASHLIYAH, 2026)
This study aims to examine the effect of the STEAM (Science, Technology, Engineering, Art, and Mathematics) approach integrated with Project Based Learning (PjBL) and PhET Interactive Simulations Build a Fraction media on students’ mathematical conceptual understanding of fractions in Grade IV elementary school. The study employed a quasi-experimental design with Nonequivalent Control Group Design. Subjects were 48 Grade IV students at SD Negeri 6 Muara Dua, divided into an experimental class (24 students) receiving STEAM-PjBL learning and a control class (24 students) receiving conventional Direct Instruction. Data were collected through pretest and posttest instruments comprising 10 valid multiple-choice items covering five conceptual understanding indicators: re-explaining concepts, identifying inter-concept relationships, applying procedures correctly, representing concepts in multiple forms, and applying concepts in contextual problems. Data analysis included descriptive statistics, Shapiro-Wilk normality test, Levene homogeneity test, and Independent Samples t-Test. Results showed the experimental class posttest mean (85.46) was significantly higher than the control class (77.75), with t = 3.579, df = 46, and Sig. (2-tailed) = 0.001 < 0.05. The STEAM approachpositively and significantly affects students’ mathematical conceptual understanding of fractions. These findings support the integration of STEAM-PjBL with interactive digital mediaas an innovative and meaningful learning strategy for elementary mathematics